Health Informatics learning objectives on an interoperable, collaborative platform - Spreckelsen, Cord; Schemmann, Ulrike; Phan-Vogtmann, Lo An; Scherag, André; Winter, Alfred; Schneider, Birgit (Stud. Health Technol. Inform., 2021)
Catalogues of learning objectives for Biomedical and Health Informatics are relevant prerequisites for systematic and effective qualification. Catalogue management needs to integrate different catalogues and support collaborative revisioning. The Health Informatics Learning Objectives Navigator (HI-LONa) offers an open, interoperable platform based on Semantic Web Technology. At present HI-LONa contains 983 learning objectives of three relevant catalogues. HI-LONa successfully supported a multiprofessional consensus process.